URINARY INCONTINENCE IN YOUNG AND NULLIPAROUS WOMEN: ASSOCIATED FACTORS AND PREVALENCE (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To verify the prevalence and risk factors associated with urinary incontinence in nulliparous young women. Methods: Integrative literature review, performed by searching the following databases: Medical Literature Analysis and Retrieval System Online (MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS), Spanish Bibliographic Index in Health Sciences (IBECS) and in the Nursing Database (BDENF), from March to June 2021, using the descriptors: “urinary incontinence”, “prevalence”, “women”, “students” and “young adult” combined with the Boolean operator “AND”. Results: The initial search resulted in 234 articles and, after applying the eligibility criteria, a final sample of 5 articles was obtained. After the analyses, a prevalence of urinary incontinence in young nulliparous women of 48% was evidenced. Risk factors were: high-impact physical activity, duration of physical activity, concomitant bowel and urinary symptoms. Conclusion: It was observed that the occurrence of urinary incontinence in nulliparous young women is a common condition. The associated risk factors demonstrate the need for health guidance to these women to avoid the chronification of the disease.